2014
DOI: 10.1177/0883073814538667
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Imaging Characteristics of Childhood Stroke in China

Abstract: There are scarce reports of childhood stroke from China. Our objective was to describe the clinical spectrum, risk factors, and imaging characteristics of childhood stroke in China. Using a hospital discharge database, children with stroke who were first admitted from 2002 to 2011 were retrospectively enrolled. We identified 478 first admissions with childhood stroke, including 229 cases of ischemic stroke and 249 hemorrhagic stroke. Boys accounted for more than 60% in all stroke types (62.2% for ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
4
18
0
Order By: Relevance
“…Our study confirms the results of previous studies describing childhood AIS as a multiple risk disease [13,16,25]. The proportion of cases with prothrombotic states exceeds the numbers reported in previous studies (0-25 %) [2,13,16,18,25,30]. It is unclear whether this reflects diagnostic bias in health care systems with structures which do not allow for the unrestrained use of laboratory diagnostics.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study confirms the results of previous studies describing childhood AIS as a multiple risk disease [13,16,25]. The proportion of cases with prothrombotic states exceeds the numbers reported in previous studies (0-25 %) [2,13,16,18,25,30]. It is unclear whether this reflects diagnostic bias in health care systems with structures which do not allow for the unrestrained use of laboratory diagnostics.…”
Section: Discussionsupporting
confidence: 85%
“…Many patients present with more than one symptom, leading to a challenge in differential diagnoses. Most of the previous reports on pediatric stroke have reported cumulative symptoms for stroke patients [2,13,18,25,30]. Characterising the leading symptoms and common symptom combinations for the different age groups of children suffering arterial ischemic stroke might allow for earlier recognition and possibly earlier diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the present study also described the same results. The most common risk factor in our series was cardiac disorders (32.5%), which is almost close to the results of the study in the Chinese population (2,12), while this number was reported nearly as twice from the previous studies in Iran (11,13). On the other hand, Masri and coworkers indicated that neurometabolic disorders were the main causes of strokes in Jordanian children (16).…”
Section: Discussion and Review Of Literaturesupporting
confidence: 72%
“…The greatest number of deaths was contributed by HS, and overall burden in childhood stroke was greater in HS than IS. There is a lack of population-based estimates of stroke incidence and mortality in developing countries although some data are available [37][38][39] , and very few that have studied temporal trends; a hospital-based study of childhood stroke showed similar proportions of HS to IS and a greater burden in men [40] . These findings reflect existing evidence on the greater burden of HS in children.…”
Section: Discussionmentioning
confidence: 99%